Value-at-Risk Analysis for the Tunisian Currency Market: A comparative study - Ben Rejeb, Aymen; Ben Salha, Ousama; Ben Rejeb, Jaleleddine (International Journal of Economics and Financial Issues, 2012)
The main purpose of this paper is to compare empirically four Value-at-Risk simulation methods, namely, the Variance-Covariance, the Historical Simulation, the Bootstrapping and the Monte Carlo. We tried to estimate the VaR associated to three currencies and four currency portfolios in the Tunisian exchange market. Data covers the period between 01-01-1999 and 31-12-2007. Independently of the used technique, the Japanese Yen seems to be the most risky currency. Moreover, the portfolio diversification reduces the exchange rate risk. Lastly, the number of violations, when they exist, does not generally differ between the simulation methods. Recent evaluation tests were applied to select the most appropriate technique predicting precisely the exchange rate risk. Results based on these tests suggest that the traditional Variance-Covariance is the most appropriate method. Keywords: Value-at-Risk; Tunisian currency market; Monte Carlo simulation JEL Classifications: C14; G32; F37